Restorative Justice in the Indonesian Legal System: Perspective of Maqāṣid al-Sharī'ah - Najib, M. Ainun; Ezbeyda, Hamed Abdelsalam Mansour (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2025)
Abstract: Restorative justice is a new paradigm in the criminal justice system that focuses on restoring social relations between perpetrators, victims, and society. This study aims to analyze restorative justice as the implementation of the values of maqāṣid al-sharī'ah in the Indonesian legal system. This research uses a normative legal approach and a descriptive qualitative method, drawing on relevant laws and regulations and Islamic legal literature. The results of the study show that the application of restorative justice in Indonesia, as stipulated in Law Number 11 of 2012, Prosecutor's Regulation Number 15 of 2020, and Police Regulation Number 8 of 2021, represents the values of ḥifẓ al-nafs, ḥifẓ al-māl, and ḥifẓ al-'ird in maqāṣid al-sharī'ah. The principles of peace (ṣulḥ), forgiveness ('afw), and social restoration are reflected in efforts to resolve cases outside the judicial channels. Thus, restorative justice not only offers a humanist and participatory legal settlement but also affirms the relevance of sharia values in the reform of national law, grounded in benefits and social justice. Keywords: Restorative justice, maqāṣid al-sharī'ah, Islamic law, benefits, Indonesian legal system. Abstrak: Keadilan restoratif merupakan paradigma baru dalam sistem hukum pidana yang menitikberatkan pada pemulihan hubungan sosial antara pelaku, korban, dan masyarakat. Penelitian ini bertujuan untuk menganalisis keadilan restoratif sebagai implementasi nilai-nilai maqāṣid al-sharī‘ah dalam sistem hukum Indonesia. Penelitian ini menggunakan pendekatan hukum normatif dengan metode kualitatif deskriptif, melalui kajian terhadap peraturan perundang-undangan dan literatur hukum Islam yang relevan. Hasil penelitian menunjukkan bahwa penerapan keadilan restoratif di Indonesia, sebagaimana diatur dalam Undang-Undang Nomor 11 Tahun 2012, Peraturan Kejaksaan Nomor 15 Tahun 2020, dan Peraturan Kepolisian Nomor 8 Tahun 2021, merepresentasikan nilai-nilai ḥifẓ al-nafs, ḥifẓ al-māl, dan ḥifẓ al-‘ird dalam maqāṣid al-sharī‘ah. Prinsip perdamaian (ṣulḥ), pengampunan (‘afw), dan pemulihan sosial tercermin dalam upaya penyelesaian perkara di luar jalur peradilan. Dengan demikian, keadilan restoratif tidak hanya menghadirkan penyelesaian hukum yang humanis dan partisipatif, tetapi juga menegaskan relevansi nilai-nilai syariah dalam pembaruan hukum nasional berbasis kemaslahatan dan keadilan sosial. Kata kunci: Keadilan restoratif, maqāṣid al-sharī‘ah, hukum Islam, kemaslahatan, sistem hukum Indonesia.